AN INDUCTIVE APPROACH TO ACCOUNTING THEORY. - Schrader, William J. (The Accounting Review, 1962)
The article presents an exploratory study of the possibility that significant generalizations about accounting might be derived inductively. Different users of inductive method might arrive at apparently unrelated generalizations about an enterprise if each were observing different aspects of its behavior, like, cultural, political, social, or technological. The method emphasizes the economic enterprise rather than its "owners" or other associated factor suppliers, and also the character of the data, and the difference between observed data per se and analyses or other manipulations of the data. Applied to accounting, it would emphasize the difference between accumulated facts and interpretations of those facts, that is, periodic or other financial statements. This might make the periodic reports more understandable. The essence of all three of these "contributions" is that inductive method clarifies the nature and limitations of accounting data and of the interpretive reports reflecting those data. Further use of the method by accounting theorists may contribute to the solution of several of the contemporary issues in accounting.